Human X‐DING‐CD4 mediates resistance to HIV‐1 infection through novel paracrine‐like signaling. (27th January 2015) - Sachdeva, Rakhee; Li, Yuchang; Shilpi, Rasheda Y.; Simm, Malgorzata
<x xml:space="preserve">Abstract</x> X‐DING‐CD4 is a novel phosphatase mediating antiviral responses to HIV‐1 infection. This protein is constitutively expressed and secreted by HIV‐1 resistant CD4+ T cells and its mRNA transcription is up‐regulated in peripheral blood mononuclear cells from HIV‐1 elite controllers. The secreted/soluble X‐DING‐CD4 protein form is of particular importance because it blocks virus transcription when added to HIV‐1 susceptible cells. The present study aimed to determine the contribution of this factor to the induction of the antiviral response in target cells. We found that soluble X‐DING‐CD4 enters cells by endocytosis and that influx of this protein induced transcription of interferon‐α and endogenous X‐DING‐CD4 mRNA in transformed CD4+ T cells and primary macrophages. Treatment of HIV‐1 susceptible cells with exogenous X‐DING‐CD4 caused depletion of phosphorylated p50 and p65 nuclear factor kappa β subunits and a significant reduction in p50/p65 nuclear factor kappa β binding to the HIV‐1 long terminal repeat. Taken together, these findings indicate a novel antiviral mechanism mediated by the influx of soluble X‐DING‐CD4, its signaling to promote self‐amplification, and functional duality as an endogenous innate immunity effector and exogenous factor regulating gene expression in bystander cells.